Analysis of Pore Water Pressure and Seepage During The Impounding Stage of Randugunting Dam - Fatimah, Illya Nur; Hidajat, Wahju Krisna; Santi, Narulita (Universitas Diponegoro, 2025)
Piping induced by seepage poses a significant risk to the stability of Randugunting Dam, located in Blora Regency, Central Java. This study aims to assess the geological and engineering geological conditions of the study area and to analyze the behavior of pore water pressure and seepage during the impounding stage. The methodology includes geological and engineering geological mapping, as well as field monitoring using instruments such as vibrating wire piezometers, v-notch, and observation wells. These field results were then compared with Finite Element Method (FEM) analysis conducted in GeoStudio SEEP/W 2018. The pore water pressure values derived from FEM analysis were generally higher than the actual values recorded by the piezometers. Groundwater levels observed in the wells showed a strong correlation with rainfall intensity. The actual seepage discharge measured at the v-notch was 0.000118 m3/sec, whereas the FEM analysis yielded a significantly higher discharge of 0.01271 m3/sec. Despite this, the measured discharge remains within safe limits, being less than 0.016 m³/s (2% of inflow) and below 0.14 l/min/m. Nevertheless, the higher discharge indicated by FEM analysis suggests a potential risk of piping that warrants attention.